Contaminated land and its reclamation - Hester, R. E.; Harrison, Roy M., 1948- (Thomas Telford, 1997)
This work deals with developments of a legal, technical and professional nature and relates these to the methods of risk assessment and their application. It discusses key developments in the UK including the Environmental Protection Act (EPA) 1990 the European Commission Green Paper on Environmental Liability and more.